Phase Transformation in ξ-Al-Ni-Rh Approximant Phase Induced by Electron Irradiation by In-situ TEM. Issue 1 (March 2020) - Zhai, Yadi; Chen, Yanhui
Abstract: Electron beam irradiation induced phase transition processes were studied on crystalline approximant phase ξ-Al-Ni-Rh in Al75 Ni15 Rh10 alloys. Approximant phase to amorphous transition phase occurred under different density of electron beam irradiation. Phase transition and separation occurred in a comparatively lower density of electron beam due to defects modulation and defects play an important role in this process. Higher density electron beam induces hollow holes with amorphous phase in the rim of the hole in the sample and face centered structure transition phase with parameter of 2.2 Å appears between the amorphous phase and ξ-phase. The appearance of the face centered structure indicates that it is the most possible shortest-range order in amorphous phase.